TEKS RANDAI UMBUIK MUDO KARYA MUSRA DAHRIZAL - Suria Dharma Eka Sakti (Jurnal Elektronik WACANA ETNIK, 2010)
This research describes the shaman practice in Umbuik Mudo randai script. This research use structure and anthropological theory. Structure analysis show that main character, Umbuik Mudo, use this practice to regain his pride. Furthermore, the object show the importance of characters status (rich and poor), pride, and behavior ethics,